DINAMIKA PERJANJIAN KONTRAK ELEKTRONIK DALAM BISNIS DIGITAL: ANALISIS KOMPARATIF DAN IMPLIKASI HUKUM - Irene Puteri Alfani Sofia Sinaga; Chionya Sherly Mahat; Grace Margareth Simarmata (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
This research aims to examine the dynamics of electronic contract agreements in digital business by conducting a comparative analysis and analyzing their legal implications. The research method used is a descriptive analytical approach by collecting data from various primary and secondary sources. The main findings of this study include the comparative analysis results between electronic contracts and conventional contracts, as well as the identification of key findings related to legal implications in digital business. The analysis results show that electronic contracts have different characteristics from conventional contracts, including in terms of proof, validity, and legal enforcement. Relevant legal implications in digital business include legal recognition of electronic transactions, consumer protection, dispute resolution, and taxation aspects. The conclusion of this study indicates the need for a deeper understanding of electronic contracts for legal practitioners, entrepreneurs, and researchers involved in digital business. The recommendations provided include the need for legal regulation adjustments, increasing public understanding of electronic contracts, and implementing appropriate legal practices in managing electronic contract agreements in digital business.